2020
DOI: 10.2217/fon-2020-0521
|View full text |Cite
|
Sign up to set email alerts
|

Belantamab Mafodotin in the Treatment of Relapsed or Refractory Multiple Myeloma

Abstract: Multiple myeloma remains an incurable disease, with a large proportion of patients in the relapsed/refractory setting often unable to achieve durable responses. Novel, well-tolerated and highly effective therapies in this patient population represent an unmet need. Preclinical studies have shown that B-cell maturation antigen is nearly exclusively expressed on normal and malignant plasma cells, thereby identifying it as a highly selective target for immunotherapeutic approaches. Belantamab mafodotin (GSK285791… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Antibody-drug conjugates (ADCs), which connected mAbs with bioactive drugs through chemical linkers ( 36 ), can accurately identify tumor cells and exert high-efficiency cytotoxic effects on malignant cells without damaging healthy tissues ( 37 ). Belantamab mafodotin (GSK2857916), which is a microtubule-disrupt agent ( 38 ), consists of humanized BCMA-targeted IgG1 and monomethyl auristatin-F (MMAF).…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…Antibody-drug conjugates (ADCs), which connected mAbs with bioactive drugs through chemical linkers ( 36 ), can accurately identify tumor cells and exert high-efficiency cytotoxic effects on malignant cells without damaging healthy tissues ( 37 ). Belantamab mafodotin (GSK2857916), which is a microtubule-disrupt agent ( 38 ), consists of humanized BCMA-targeted IgG1 and monomethyl auristatin-F (MMAF).…”
Section: Progress Of Bcma-targeted Immunotherapiesmentioning
confidence: 99%
“…Belantamab mafodotin (BM) is the first-in-class humanized afucosylated anti-BCMA IgG1 ADC, recently approved by the US Food and Drug Administration (FDA) for monotherapy in patients with relapsed or refractory MM (RRMM) [ 24 , 35 , 36 ]. Initial data in a multicenter phase I trial (DREAMM-1) in heavily pretreated (pronounced PIs and IMiDs) RRMM patients showed that BM (BMA117159) was effective with ORR of 60% (14% CR, 60% very good partial response (vgPR)) and PFS of 12 months [ 37 ] with a manageable side effects profile.…”
Section: Bmca-targeted Treatment In MMmentioning
confidence: 99%
“…The third one is the ICD (immunogenic cell death), through the expression of antigens specific to dying tumor cells. 65 …”
Section: “Old” Generation Immunotherapiesmentioning
confidence: 99%